Method of agricultural sewage water purification at troughs and a biosorption bioreactor - Matsak, Anton; Tsytlishvili, Kateryna; Rybalova, Olga; Artemiev, Sergey; Romin, Andrey; Chynchyk, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2018)
We proposed a method for sewage water purification of nitrogen and phosphorus compounds on a disk bioreactor of full displacement. The developed method of sewage water purification on a bioreactor of full displacement is very promising and we can use it for purification of sewage water, which contains a large amount of organic substances. The efficiency of purification of mineral nitrogen reaches 98.9 %, phosphates up to 40‒50 %. The total nitrogen content decreases by 4‒6 times and the total phosphorus content ‒ by 2‒2.5 times. We proposed combined purification of surface runoff from agricultural land and household or industrial sewage water on troughs with filtering nozzles and on a bioreactor of full displacement. The conducted microbiological studies showed that the process of purification removes nitrogen compounds complexly: as a result of nitrite-denitrification and of the process of anoxide oxidation. We observed transformation of nitrogen mineral compounds under nitrification on the surface of biodisks in presence of oxygen and inside structural elements of biodisks, which is characteristic of anoxide oxidation during ANAMMOX process. Efficiency of purification of sewage water from the territories for agricultural purposes makes up: for suspended substances ‒ 98 %; for mineral nitrogen ‒ 99 %; for CCO ‒ 99 %; for phosphates ‒ 50 %. We can use the scheme of purification on troughs and a bioreactor of full displacement for sewage water of dairy industry, livestock farms, communal services, and surface runoff. Application of the proposed methods of sewage water purification will contribute to improvement of aquatic ecosystems